1988
DOI: 10.1126/science.3420417
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Phosphorescence: A Novel Method for Measuring Oxygen Distribution in Perfused Tissue

Abstract: The imaging of phosphorescence provides a method for monitoring oxygen distribution within the vascular system of intact tissues. Isolated rat lives were perfused through the portal vein with media containing palladium coproporphyrin, which phosphoresced and was used to image the liver at various perfusion rates. Because oxygen is a powerful quenching agent for phosphors, the transition from well-perfused liver to anoxia (no flow of oxygen) resulted in large increases of phosphorescence. During stepwise restor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
289
0
4

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 477 publications
(297 citation statements)
references
References 4 publications
1
289
0
4
Order By: Relevance
“…The probe binds to albumin and is therefore localized to the plasma phase of the intravascular compartment. In blood, the only molecule that quenches phosphorescence is O 2 (15); thus the lifetime of the phosphorescence originated by excitation of the phosphor is determined by plasma PO 2 . The value of Pm O 2 obtained in …”
Section: Discussionmentioning
confidence: 99%
“…The probe binds to albumin and is therefore localized to the plasma phase of the intravascular compartment. In blood, the only molecule that quenches phosphorescence is O 2 (15); thus the lifetime of the phosphorescence originated by excitation of the phosphor is determined by plasma PO 2 . The value of Pm O 2 obtained in …”
Section: Discussionmentioning
confidence: 99%
“…Measuring phosphorescence intensity and lifetime allows quantification of oxygen concentrations (Rumsey et al 1988;Vanderkooi et al 1990). In the case of imaging of cells, this can be accomplished on a pixel-by-pixel basis by applying phasemodulation methods.…”
Section: Figure 10mentioning
confidence: 99%
“…Based on these phosphorescent properties, porphyrin derivatives have been used as optical oxygen sensors in the aerodynamics field (3,4). It has also been reported that PdTCPP can be used to measure the oxygen concentration in normal tissues (5), in cancer cells (6), or in blood (7). However, the physiological properties of PdTCPP are still unclear.…”
mentioning
confidence: 99%